Pengaruh PAD, Indeks Pembangunan Manusia dan Tingkat Pengangguran Terbuka terhadap PDRB Kabupaten/Kota Bali 2019-2023 - I Made Danu Artha; Ni Ketut Budiningsih (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
Regional economic development has become one of the main priorities in improving community welfare, with the Gross Regional Domestic Product (GRDP) serving as the primary indicator of economic growth. The Province of Bali has recorded relatively high aggregate economic performance; however, there remain significant disparities among its regencies and municipalities. This study aims to analyze the effect of Regional Own-Source Revenue (PAD), Human Development Index (HDI), and Open Unemployment Rate (OUR) on the GRDP of regencies and municipalities in Bali during the 2019–2023 period. A quantitative approach was employed using secondary data obtained from the Central Bureau of Statistics (BPS) of Bali Province. The analysis was conducted using panel data regression to examine both the simultaneous and partial effects of the independent variables on GRDP. The results indicate that PAD, HDI, and OUR simultaneously have a significant effect on GRDP. Partially, PAD and HDI exert a positive influence, suggesting that higher regional revenues and better human resource quality contribute to the economic growth of regencies and municipalities. Conversely, OUR shows a negative effect, implying that a higher unemployment rate decreases GRDP. These findings highlight the importance of optimizing regional revenues, improving human resource quality, and enhancing employment absorption as strategic efforts to foster sustainable economic growth and reduce regional disparities in Bali. This study is expected to serve as a valuable reference for local governments in formulating more effective and equitable economic development policies, as well as in understanding the key factors influencing economic performance across regencies and municipalities.